Bowen’s disease – a review of newer treatment options - Thorsten Neubert; Percy Lehmann (Dove Medical Press, 2008)
Thorsten Neubert, Percy LehmannZentrum für Dermatologie, Allergologie und Umweltmedizin, Helios Klinikum Wuppertal, Klinikum der Universität Witten-Herdecke, Wuppertal, GermanyAbstract: Bowen’s disease (squamous cell carcinoma in situ) has a 3%–5% risk to develop into invasive squamous cell carcinoma. Non-melanoma skin cancer is the most common cancer among Caucasians and its incidence has increased during the last decades dramatically. Multiple treatment options for Bowen’s disease have been described and are established with advantages and disadvantages. Bowen’s disease occurs more often in elderly patients (with a higher risk of comorbidities) and is frequently located on body sites with poor wound healing. Therefore there is need for non-invasive/non-destructive but effective treatment options. We would like to give an overview of established therapies and more detailed information about the newer treatment options for Bowen’s disease with topical diclofenac, topical imiquimod and photodynamic therapy.Keywords: Bowen’s disease, photodynamic therapy, imiquimod, diclofenac